471PChemotherapy in advanced thymic malignancies. (24th November 2019) - Varshney, A N; Vanidassane, I; Ramavth, D; Malik, P S; Khurana, S; Garg, V; Vadlamani, S P; Kalra, K; Gunasekar, S; Kumar, S; Sethi, S; Yadav, M; et al.
Abstract: Background: Despite being a rare disease entity, Thymoma and Thymic carcinomas represent the most common cause of anterior mediastinal mass. Clinical course is widely varied from an indolent course to florid metastatic disease with paraneoplastic manifestation. Treatment guidelines are based on small phase 2 studies. Data of chemotherapy in advanced thymoma is limited. Methods: It is a retrospective study of advanced thymic epithelial tumors treated with chemotherapy over a period of 7 years (2011 -2017). All patients with unresectable /metastatic thymic tumours and who have received chemotherapy as were included in the study. Independent review of radiology images and histopathology slides were performed. Results: There were 55 cases registered with thymic malignancy and 32 cases were analyzed for present study. Among them 27 cases were thymoma, 3 were thymic carcinoma and 2 were thymic NET. The median age was 39 years (22 65 years). Male: female ratio was 3: 1. The median duration of symptoms was 5.9 months (0-36 months). Twelve cases (38%) had features of superior vena cava obstruction at presentation. The mean size of mediastinal mass was 8.9 + 3.26 (range 2-15 cm). More than half of the cases (56%) showed calcification. Mediastinal lymph nodes were seen in 14 patients (46%). There was pleural involvement in 14 patients (73%) and pericardial involvement in 13 cases (43%). Pleural effusion was seen in 17(53%). Only 5 cases had stage III, 18 had stage Iva and 9 had stage IVb disease. The most common histological subtype as per WHO classification was B1 in 11 patients (34%) followed by B3 in 9 patients (28%) in our cohort. Out of 32 cases 3 have had upfront R2 resection. Post chemotherapy, one case attained CR, 10 had PR, 13 had SD and 3 had PD. 6 cases underwent surgery post induction therapy. 3 had R1 resection and 3 had R2 resection. Cisplatin, doxorubicin and cyclophosphamide (CAP) remains first choice for chemotherapy in 81% patients followed by paclitaxel-carboplatin in 12.5%. Radiation therapy was given to 13 patients. After a median follow up of 24.86 months, median PFS is 16.1 months and median OS was not reached. Conclusions: Thymic malignancies are a heterogeneous group of disorders. Multi-modality treatment including chemotherapy is an effective and feasible treatment for advanced thymoma. Legal entity responsible for the study: All authors are equally responsible. Institute ethics committee has given the clearance. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.